دراسة تحليلية لمشكلة البطالة و العوامل المؤثرة فيها في سورية خلال الفترة 1980-2008 - الشيخ حسين صطوف (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يسعى هذا البحث إلى تحليل ظاهرة البطالة Unemployment في سورية خلال الفترة 1980-2008 والتركيز على الخمس عشرة سنة الأخيرة التي تفاقمت فيها مشكلة البطالة في سورية. ففي هذا البحث تمت دراسة المفاهيم المختلفة للبطالة وطرق قياسها، وتحليل تطورها وعلاقتها مع النشاط الاقتصادي ودخل الفرد وتم التركز على بنية البطالة في سورية وذلك حسب الجنس وحسب التركيب العمري وكذلك حسب المستوى التعليمي وحسب المحافظة. وفي النهاية تم تقديم نموذج اقتصاد قياسي، من نوع انحدار خطي متعدد، لتحديد الأهمية النسبية للعوامل الاقتصادية والاجتماعية المؤثرة في هذه الظاهرة. تبين، من خلال هذا النموذج، أن سياسة الانفتاح الاقتصادي وكذلك سياسة الإصلاح تركا أثر واضح على ظاهرة البطالة بالإضافة إلى حصة الفرد من الناتج المحلي الإجمالي. كانت العلاقة واضحة بين الانفتاح الاقتصادي والبطالة في بداية التسعينات بعد إدخال قانون الاستثمار رقم/10/ للعام 1991 ولكن سرعان ما تلاشى ذلك الأثر ولم يبقى سوى أثر تحرير التجارة مما أدى إلى وجود علاقة طردية بين الانفتاح ومعدل البطالة. أما الإصلاح الاقتصادي في سورية فإنه لم يترافق بإعادة هيكلة وتسريح للعمالة الفائضة، لذلك، لم يترك إلا أثر بسيط على البطالة، من خلال سياسة التوظيف في القطاع العام التي تراجعت بشكل واضح، لذلك أدت سياسة الإصلاح الاقتصادي إلى زيادة معدل البطالة. أما العوامل الاقتصادية والاجتماعية الأخرى مثل معدل نمو الاستثمارات الخاصة والأجور ومعدل نموها ومعدل نمو السكان تم حذفها من النموذج لعدم وجود المعنوية الإحصائية. This research seeks to analyze the phenomenon of unemployment in Syria during the period 1980-2008 and focus on the last fifteen years, where the problem of unemployment in Syria was exacerbated. In this paper, the different concepts of unemployment and its measurement methods are analyzed, although the analysis of its development and its relationship with economic activity and per capita income, and we focused on the structure of unemployment in Syria, by gender and by age structure as well as by level of education and by governate. At the end, an econometric model, of multiple linear regression type, has been identified to determine the relative importance of economic and social factors affecting the problem of unemployment. Through this model, we found that the policy of economic liberalization, as well as the reform policy and the per capita income, have had a demonstrable impact on the phenomenon of unemployment. The relationship between the economic liberalization and the unemployment was evident at the early 1990s after the introduction of the Investment Law number /10/ in 1991, but that impact has quickly faded and only the impact of the trade liberalization has persisted, which led to a direct positive correlation between the liberalization and the unemployment rate. But the economic reform in Syria was not associated with the restructuring and the layoffs of workforce surplus; therefore, it has had only a little impact on the unemployment through the employment policy of the public sector which has retreated significantly. For this reason, the economic reform policy has leaded to an increase in the unemployment rate. Other factors such as the private investments growth rate, wages and its growth rate and the population growth rate has been deleted from the model as they are statistically not significant.